Implementation of Social Media Management PT. Toyota Astra Financial (TAF) MEDAN to Increase Awareness - Girsang, Aulia Anggraini; Fikri, Miftah El (Economic: Journal Economic and Business, 2025)
This study aims to analyze the Instagram social media management strategy of PT. Toyota Astra Financial (TAF) Medan in increasing the effectiveness of information delivery and brand awareness through a content marketing approach. The strategies implemented include goal setting, target market mapping, content planning and creation, distribution, reinforcement, evaluation, and content improvement. The method used is descriptive qualitative with data collection techniques in the form of observation, documentation, and semi-structured interviews. The success of the strategy is analyzed through Instagram Insight data with indicators of accounts reached, accounts engaged, and number of followers. The results show that the management of the @taf.medanbranch account has succeeded in increasing account reach to 5,948 accounts, interactions of 208 accounts, and increasing followers to 156 followers. The implementation of a content marketing strategy has proven effective in expanding audience reach, increasing user engagement, and strengthening the delivery of company information through social media. These results indicate the importance of a planned content strategy in building connectedness with audiences in the digital era.